Bird Survey At Sungai Dusun Wildlife Reserve, Perak, Malaysia - Zahirunisa, Abd Rahim; Wan Nurainie, Wan Ismail; Nur Aida, Md Tamrin; Mohd Hanif, Ridzuan Mat Daud; Madinah, Adrus; Huzal Irwan, Hussin; M.A., Rahman; M.T., Abdullah (Department of Wildlife and National Parks (DWNP) Peninsular Malaysia, 2014)
A survey on birds was conducted at Sungai Dusun Wildlife Reserve on the 26th until 31th of October 2009. Ten mist nets were deployed throughout the four days sampling period. A total of 27 individuals representing 16 species from 10 families of birds were recorded. The most common species recorded is the Arachnothera longirostra that was represented by six individuals.